Pengaruh TINGKAT PENGETAHUAN PASIEN DIABETES MELITUS TIPE II RAWAT JALAN TERHADAP KEPATUHAN TERAPI OAD DI PUSKESMAS KABUPATEN GIANYAR SELAMA PANDEMI COVID-19 - Tresnayanthi, Kadek Ayu Sri; Mahendra, Agung Nova; Indrayani, Agung Wiwiek; Sumardika, I Wayan (E-Jurnal Medika Udayana, 2023)
Type II Diabetes Mellitus dominates DM cases in primary health care. The limitations type II DM services during the COVID-19 pandemic by Puskesmas risk decreasing the level of knowledge and adherence to OAD therapy in type II patients. A good level of patient knowledge about type II DM can influence a patient’s decision to comply with OAD therapy during the COVID-19 pandemic. This study aims describe effect of knowledge level type II Diabetes Mellitus patients on OAD therapy adherence at Gianyar district health center during the COVID-19 pandemic. The method used analytic method with a cross-sectional approach during the period March-August 2022 in four health centers of Gianyar regency. The level of measurement using the Diabetes Knowledge Questionnaire (DKQ-24) and therapeutic compliance with the Morisky Medication Adherence Scales (MMAS-8) questionnaire, the data was taken using google form.Based level knowledge 96 respondents (43,7%) high knowledge, 46 people (48%) moderateknowledge, and 8 people (8,3%) low knowledge. Meanwhile based on level of compliance, there were 53 people (55,2%) with hight compliance, 35 people (36,5%) with moderate compliance, and 8 people (8,3%) with low compliance. The level knowledge and compliance to patients during COVID-19 was moderate knowledge and high compliance, may be influenced by the ease of access to information for patients in internet. Outpatient type II DM at the Gianyar district health center during the COVID-19 pandemic moderate knowledge and high compliance, and there was a significant effect between the level of knowledge to therapy adherence and a p-value of 0,000. Keywords : knowledge, compliance, influence, diabetes mellitus type II, pandemic COVID-19.